ANALISIS EOQ (ECONOMIC ORDER QUANTITY) DALAM PENGENDALIAN BAHAN BAKU PADA CV. WETY PAPUA KABUPATEN MANOKWARI - Suruan, Ted Matheus; Prasetyp, Indra; Sudarwadi, Dirarini (Cakrawala Management Business Journal, 2024)
ABSTRACT This Reasearch aims to determine the analysis of raw material supply control, the most economical amount of raw material purchases and the right time to reorder and to find out the relationship between costs, sales units and profits using the EOQ (Economic Order Quantity) method. This research is a type of descriptive research with a quantitative approach. This study used primary and secondary data types. The subject in the study was a CV. Wety Papua and the object of this study is the analysis of EOQ (Economic Order Quantity) in controlling raw materials on CV. Wety Papua. Data collection techniques carried out with Literature Studies, observations, interviews, and documentation. Data analysis using field analysis of EOQ models. The results of this study show that the control of raw materials on CV. Wety Papua is less efficient because there is a remaining supply of cement raw materials of 56 sack and 47.7 m3, so there is an excess of raw materials, while using the EOQ method will be more economical and there are no remaining raw materials.